2017
DOI: 10.47611/jsr.v6i1.286
|View full text |Cite
|
Sign up to set email alerts
|

Sex and longevity: Why women live longer than men.

Abstract: Sex differences in lifespan exist in most countries in the world, with women outliving men. This difference has existed for as long as records have been kept.  This gap is not a uniquely human phenomenon; it exists in many animals as well.  This is an important health issue that is not fully understood.  Aging is a complex process.  In this review we will examine the scientific basis for sex differences by focusing on four hypotheses that begin with examining why women are different from men.  Men and women di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Elderly people's lack of mobility can result in disengagement from civic and social life, resulting in loneliness and poor quality of life in general (Dickerson et al 2007). Most elderly people are women (Peck et al 2017) and, in developed countries, differences in access to a car are more apparent in generations where fewer women had a driver's licence. When elderly women start suffering from physical problems that make walking more difficult and no longer have a man at their side who drives, they often become isolated, especially in rural areas where PT services are weak (Duchène 2011).…”
Section: Discussion and Best Practicesmentioning
confidence: 99%
“…Elderly people's lack of mobility can result in disengagement from civic and social life, resulting in loneliness and poor quality of life in general (Dickerson et al 2007). Most elderly people are women (Peck et al 2017) and, in developed countries, differences in access to a car are more apparent in generations where fewer women had a driver's licence. When elderly women start suffering from physical problems that make walking more difficult and no longer have a man at their side who drives, they often become isolated, especially in rural areas where PT services are weak (Duchène 2011).…”
Section: Discussion and Best Practicesmentioning
confidence: 99%
“…This study identified a mostly positive relationship between the two factors; however, after at the age of 91 or older, the prevalence of AD and dementia dropped to 4.71%, the lowest proportion seen since those in the 46 to 50.9 years of age category. One possible explanation of this result is that women tend to live longer and healthier lives than men (Peck et al, 2017).…”
Section: Chapter 5: Discussion and Conclusionmentioning
confidence: 99%
“…There are three prevailing hypotheses as to why this is the case (Peck et al, 2017). The heterogametic hypothesis states that women have two X chromosomes, which provides genetic redundancy when mutations occur.…”
Section: Chapter 5: Discussion and Conclusionmentioning
confidence: 99%